PENGARUH PENERAPAN MODEL TWO STAY TWO STRAY TERHADAP KETERAMPILAN BERKOMUNIKASI DAN HASIL BELAJAR SISWA PADA MATERI STRUKTUR ATOM - Nikmatus Sa'adah (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2021)
Abstract This research was instigated by Chemistry learning at State Senior High School 12 Pekanbaru dominated by discussion method and the low of student score on Atomic Structure lesson in the Academic Year of 2018/2019.  It aimed at knowing the effect of implementing Two Stay Two Stray model toward student communication skill and learning achievement on Atomic Structure lesson.  It was an Quasy Experimental research with True Experimental Pretest Posttest Control-Group design.  Random Sampling was used in this research.  The samples of this research were the tenth-grade students of MIPA 2 as the Control group and the students of MIPA 5 as the Experimental group.  The instruments of collecting the data were learning achievement test and questionnaire that was supported by observation sheet and documentation.  Based on the research findings of learning achievement, it was obtained that tobserved was 3.41 and ttable was 2.00, and it showed that tobserved was higher than ttable.  It showed that there was an effect on learning achievement, and the effect was 14.2%.  Based on the research finding of communication skill, it was obtained that tobserved was 2.95 and ttable was 2.00, and it showed that tobserved was higher than ttable.  It showed that there was an effect on communication skill and the effect was 11%. Keywords : Two Stay Two Stray Model, Communication Skill, Learning Achievement, Atomic Structure.